Mortality study of nickel platers with special reference to cancers of the stomach and lung, 1945-93. Issue 10 (October 1996) - Pang, D; Burges, D C; Sorahan, T
Abstract : OBJECTIVES: To re-examine mortality patterns in a cohort of nickel platers with no history of chromium plating. METHODS: All 284 men first employed by the company in 1945-75 with a minimum employment of three months in the nickel plating department were identified. Workers who had worked in the chromium plating or nickel/chromium plating departments were excluded. Standardised mortality ratios (SMRs), P values, and 95% confidence intervals were calculated. Poisson regression was used to carry out statistical modelling of mortalities within the cohort (internal standard). Four variables were considered to have the potential to influence mortality within the cohort: attained age (age at follow up or age at death), year of starting nickel work, period of follow up (measured from the first period of work with nickel exposure), and duration of exposure to nickel. RESULTS: The only significant difference between observed and expected numbers, when investigated by site of cancer and by broad non-cancer groupings, was that for stomach cancer (observed eight, expected 2.49, SMR 322). CONCLUSIONS: The study provides only weak evidence that nickel plating is associated with an excess risk of stomach cancer. This cohort of nickel platers does not seem to have experienced any discernible risk of occupational lung cancer. Other studies of nickel platers rather than nickel/chromium platers would be useful.